Biomimetic extracellular environment based on natural origin polyelectrolyte multilayers - Silva, Joana Maria Marques (2016)
Surface modifi cation of biomaterials is a well-known approach to enable an adequate biointerface between the implant and the surrounding tissue, dictating the initial acceptance or rejection of the implantable device. Since its discovery in early 1990s layer-by-layer (LbL) approaches have become a popular and attractive technique to functionalize the biomaterials surface and also engineering various types of objects such as capsules, hollow tubes, and freestanding membranes in a controllable and versatile manner. Such versatility enables the incorporation of different nanostructured building blocks, including natural biopolymers, which appear as promising biomimetic multilayered systems due to their similarity to human tissues. In this review, the potential of natural origin polymer-based multilayers is highlighted in hopes of a better understanding of the mechanisms behind its use as building blocks of LbL assembly. A deep overview on the recent progresses achieved in the design, fabrication, and applications of natural origin multilayered films is provided. Such films may lead to novel biomimetic approaches for various biomedical applications, such as tissue engineering, regenerative medicine, implantable devices, cell-based biosensors, diagnostic systems, and basic cell biology.